Tanggung Jawab Orang Tua Dalam Mengasuh Anak (Studi Analisis Qur’an Surat Luqman Ayat 12-19) - Rika - Sa'diyah; Siti Shofiyah; Kurniawan Mansyur; Anisah Meidiana (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2022)
Currently, generations have been grouped into various generation groups according to the year of birth, if sorted from the earliest birth year, there is such a thing as the Baby Boomer Generation, Generation X or Baby Bust, Millennial Generation or Generation Y and the latest is Generation Z. Generation Z. Millennials and Generation Z are the generations that dominate today, because almost both generations live in an era where all use technology. The rapid development of today's era is one of the duties of parents to accompany their children so as not to fall into something wrong. However, the current situation is in line with what is feared. All children are so connected and controlled by the internet that they cannot filter which ones are suitable or not to be consumed. This is due to the negligence of parents in carrying out their duties and responsibilities. Even most parents do not know what is the main responsibility as parents to their children, even though it is very clear that Allah SWT says in the Koran, the main way of life for a Muslim. For this reason, this research is expected to provide a wealth of knowledge to enlighten parents.